National Language Planning and Language Shifts in Malaysian Minority Communities Speaking in Many Tongues - Mukherjee, Dipika (Amsterdam University Press, 2011)
Controversies and problems with regard to language policy and language education still exist in Malaysia. Despite the attempts of language policy makers to promote multilingualism, the implementation has been marred by political and religious affiliations. Malaysia is a melting pot of many different cultures and ethnicities, the three largest being Malay, Chinese and Indian. Therefore, an analysis of the language variation in this polyglot nation will help in understanding the variety of languages and those who speak them. This book gathers the work of researchers working in the field of language change in Malaysia for over two decades. As there is no book published internationally on the language policy in Malaysia and the effects on the language change in urban migrant populations, this book is a timely contribution not only to an understanding of Malaysian linguistic pluralism and its undercurrents, but also to an understanding of the Indian Diaspora.